A importância da interação social para o funcionamento do sistema circadiano de camundongos - Paola Fernandes (2017)
Social isolation induces several changes in humans and rodents. In the latter, changes in mood-related behaviors are highlighted. Mood disorders, such as depression, are accompanied by changes in various circadian rhythm parameters. The suprachiasmatic nucleus of the hypothalamus (SCN) directs the circadian rhythms, such as the rhythms of spontaneous locomotor activity (SLA) and core body temperature (Tcore), which in turn are entrained by cycles of light and darkness, which is critical for our clock to anticipate, internally, the changes in the external environment in order to adjust our behavior and metabolism. In addition to light, non-photic stimuli, such as social interaction, seem to contribute to the synchronization of the biological clock. In this study, we evaluated the impact of loss of social interaction on mood-related behaviors; as well as on the circadian rhythms of SLA and Tcore, plasticity of the circadian system, and neuronal activity of NSQ. Male C57BL / 6J male mice were kept isolated or grouped for 4 weeks in light:dark cycles of 12:12 h. A telemetry sensor was implanted in the intraperitoneal cavity on the 15th day of the protocol to analyze the circadian rhythms of SLA and Tcore. In order to evaluate whether the photo-entrainment response is affected by isolation, the animals were subjected to a jetlag protocol, where the light phase was advanced for 6 h from the 29th to the 35th day (lights on at 11:00 a.m. and lights off at 11:00 p.m.), and from the 36th day to the 42th, the light phase was delayed by 6 h (lights on at 5:00 a.m. and lights off at 5:00 p.m.). One group of animals under light:dark cycles of 12:12 h was transcardially perfused on ZT2 and ZT14 for analysis of c-Fos expression in the SCN. Another set of isolated and grouped animals were tested for the behavioral despair, anhedonic like behavior and anxious like behavior through forced swimming tests, sucrose preference test, and elevated plus maze, respectively. The experiments were approved by UFMG Ethics Committee (nº 12/2015). The social isolation protocol used in this study induced behavioral despair and hedonic seeking behavior to sucrose, but not anxiety-like behavior. A significant loss in body weight gain was also observed in the isolated group along with social isolation period. In addition, social isolation induced a decrease in total SLA both in the light and dark phase, as well as an increase in the amplitude of the Tcore rhythm. Although there were no changes in the onset, offset and acrophase of SLA, social isolation caused an advance in the Tcore onset, as well as a delay in the offset of the Tcore rhythm. Thus, social isolation causes an uncoupling of the SLA and Tcore rhythms. In agreement with these results, the temporal activity of SCN neurons was lost after isolation. In addition, socials isolation seems to impair the photo-entrainment responses, since the isolated animals showed a faster entrainment of their SLA onset compared to grouped animals. These results indicate that loss of social interaction causes disturbances in the SLA and Tcore circadian rhyhtms and affects the photo-entrainment mechanisms through disturbances in the central clock function, what may cause mood-related changes.